Novel treatment of coronary artery fistulae concealing severe coronary artery lesion: using thrombus aspiration catheter as a delivery guide - Korkmaz, Levent (Science Press, 2014)
In this case report, we present the occlusion of multiple coronary artery fistulae originating from proximal left anterior descending (LAD) and right sinus valsavla and empting to the pulmonary artery at the same place. We occluded LAD fistulae by using thrombus aspiration catheter as a delivery guide. To the best of our knowlege, this is the first case of occlusion of coronary fistulae with the help of thrombus aspiration catheter. Our experience may suggest that thrombus aspiration catheters can be used in treating coronary artery fistulae with difficult anotomy.